2021
DOI: 10.1111/joa.13495
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of living longer—Effects of an experimentally extended velvet antler phase on the histomorphology of antler bone in fallow deer (Dama dama)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The present study demonstrated the regular presence of calcified cartilage remnants in the distal portions of hard antlers from all three studied species, thereby confirming the results of previous studies ( Landete-Castillejos et al, 2012 ; Kierdorf et al, 2013 , Kierdorf et al, 2021 ). In the late-formed, distal antler regions, resorption of the framework of calcified cartilage was thus typically incomplete, while further proximally the cartilage was largely or entirely replaced by bone in the course of antler histogenesis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study demonstrated the regular presence of calcified cartilage remnants in the distal portions of hard antlers from all three studied species, thereby confirming the results of previous studies ( Landete-Castillejos et al, 2012 ; Kierdorf et al, 2013 , Kierdorf et al, 2021 ). In the late-formed, distal antler regions, resorption of the framework of calcified cartilage was thus typically incomplete, while further proximally the cartilage was largely or entirely replaced by bone in the course of antler histogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…The persistence of calcified cartilage in the distal antler regions and the lack of any significant remodeling of the antler bone are regarded as the inevitable consequence of the short (only few months) lifespan of antlers ( Kierdorf et al, 2021 ). The latter view is supported by the observation (in fallow deer) that when the lifespan of antlers is experimentally extended by antiandrogen treatment, the calcified cartilage in the antler tips is completely replaced by bone in the course of marked remodeling ( Kierdorf et al, 2021 ). Further evidence of this process was the frequent presence of secondary osteons and resorption cavities in the antler bone of the experimental animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations